2009
DOI: 10.1155/2009/934698
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Universal Prophylaxis in Pregnancy with Prior Group B Streptococci Colonization

Abstract: Objective. To estimate the costs and outcomes of rescreening for group B streptococci (GBS) compared to universal treatment of term women with history of GBS colonization in a previous pregnancy. Study Design. A decision analysis model was used to compare costs and outcomes. Total cost included the costs of screening, intrapartum antibiotic prophylaxis (IAP), treatment for maternal anaphylaxis and death, evaluation of well infants whose mothers received IAP, and total costs for treatment of term neonatal earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…A Dutch study [35] found a combined screening and risk-based study to be very cost-effective, while for screening alone the cost per QALY was around twice the GNP per head, rendering it just cost-effective. In addition, a recent USA article suggests that universal treatment of term pregnancies with a prior history of GBS colonization is more cost-effective than a strategy of screening and treating based on positive culture results [36]. …”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study [35] found a combined screening and risk-based study to be very cost-effective, while for screening alone the cost per QALY was around twice the GNP per head, rendering it just cost-effective. In addition, a recent USA article suggests that universal treatment of term pregnancies with a prior history of GBS colonization is more cost-effective than a strategy of screening and treating based on positive culture results [36]. …”
Section: Discussionmentioning
confidence: 99%
“…A strategy providing intrapartum chemoprophylaxis without prior screening to all women who were GBS-colonized in a previous pregnancy was evaluated hypothetically in a decision analysis, finding that culture avoidance and uniform treatment might be cost-effective. 20 However, that study took into account only two prior small studies to determine the risk of recurrent colonization. The study was further limited by the use of manufacturer's suggested price instead of actual drug prices for penicillin and by the assumption that all patients would be treated with penicillin instead of ampicillin or other antibiotics in the setting of penicillin allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous economic studies of neonatal EOS have focused on the costs associated with maternal screening, intrapartum prophylaxis, or neonatal GBS disease [24][25][26][27][28] with little attention to the costs of neonatal evaluation. The resources expended over the study periods among asymptomatic infants at risk for EOS were considerable; more than 2200 nursing hours were required to evaluate 1396 infants, including 890 uninfected infants treated with antibiotics, at an estimated cost of nearly $400 000.…”
Section: Discussionmentioning
confidence: 99%